Postgraduates students' utilization of the ict: implications on academic achievement (2016)
ICT usage patterns among students including use of the internet is increasingly being investigated. One area of interest for educators relates to the home use of the computer and the internet by postgraduate students and its relationship to academic achievement. This is particularly relevant as the amount of time that postgraduate students spend at home on the computer appears to be rising. This trend may have an impact on academic performance and their research initiative and prowess. The purpose of this study was to examined postgraduate's uses and utilization of the internet and its implication on their achievement at the University of Ibadan. Two hundred and fifty postgraduate students from twenty systematical selected departments formed the study sample. A modified internet use scale was used to gather data for the study. The data collected was analysed using descriptive statistics, chi-square and Freidman test. The results indicate that; majority of the respondents access the internet 1-5 hours per week, some access the internet 6-20 hours per week while others access the internet between 21-25 hours per week. Further to these, most respondents use the internet for the purpose of obtaining course related information and to enrich their research. The results also reveal that internet contributes significantly to academic achievement of the respondents. The study recommends among others the provision of more computers and internet facilities at library and postgraduate school to compliment the existing few provided.